The Representation of Taoism Ethical Values in the Dao De Jing and Their Relevance in the Film “Nezha: Birth of the Demon Child” - Abimanyu Abimanyu; Fatmawati Fatmawati; Tri Wahyu Retno Ningsih (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2026)
Film as a contemporary medium has the capacity to convey philosophical values to the present generation. This study aims to analyze the ethical values of Taoism in the Chinese animated film Nezha: Birth of the Demon Child from the perspective of the Dao De Jing. The research employs a qualitative approach with content analysis methods. Data were collected through observation and note-taking techniques, then analyzed using the Miles and Huberman (2014) model. The primary source of analysis is the Dao De Jing 道 德 经 (dào dé jīng), the teaching of laozi in its English translation, referring to Yao, Chen, and Song (2017), who identified eight Taoism ethical values: a merciful and loving heart, be frugal, honest, and simple, be humble, non-action, gentleness, authenticity, harmony, and nurture. The findings reveal three main points. First, seven ethical values are identified, with a merciful and loving heart emerging as the most dominant in character formation. Second, the moral message emphasizes that sacrifice for the common good is more valuable than personal ambition, that cooperation can overcome differences, and that moral education transforms character. Third, the film Nezha demonstrates the continuing relevance of Taoism ethics in the Dao De Jing for addressing social issues in modern society.